Analyse de la variabilité climatique et de ses influences sur les régimes pluviométriques saisonniers en Afrique de l’Ouest : cas du bassin versant du N’zi (Bandama) en Côte d’Ivoire - Amani Michel Kouassi; Koffi Fernand Kouamé; Yao Blaise Koffi; Kouakou Bernard Dje; Jean Emmanuel Paturel; Sekouba Oulare (Cybergeo, 2010)
The climate variability was generally studied in West Africa and particularly in Ivory Coast. The rainfall variability was specifically analysed. Therefore, rainfall variables such as rainy days frequency and rainfall seasonal duration are little studied. The main purpose of the following work is to show the climate influence on seasonal rainfall regimes on the N’zi (Bandama) watershed. We have documented two main aspects of climate variability. In the first part, the climate variability was characterised by the analysis of air temperature, air humidity, rainfall index, rainfall days frequency and seasonal rainfall duration. In the second step, we compared the standard monthly rainfall for 1951-2000 period so as to analyse the behaviour of seasonal rainfall regimes in the climate variability context. An analysis in normalized principal components (ANPC) allowed the analysis of the impact of the climatic factors on the seasonal rainfall regimes. The climate variability was manifested by a decline of the spatial and temporal annual rainfall, a decrease of rainfall days frequency particularly those which are superiors to 10 mm and a reduction of rainfall seasonal duration (30 to 35 days) since 1970. In this study, the most important result of our investigations is the lack of change in the monthly rainfall regimes on the N’zi (Bandama) watershed. The analysis in normalized principal components (ANPC) based on fourteen (14) variables, made it possible to highlight the impact of climate variability on the seasonal rainfall regimes. The first and main component (F1) is associated with the factors defining the atmospheric conditions. The second and third components (F2 and F3) are associated with the variables related to precipitations. As for the factors which influence the temporal variability of the seasonal pluviometric regimes, it appeared that the six rainfall variables are influenced by air temperature as well as the relative humidity of the air. It was thus concluded that air temperature and the relative humidity of the air are factors of the temporal variability of the seasonal rainfall regimes on the N’zi (Bandama) watershed.